Peran Strategi Coping Dalam Memediasi Pengaruh Stres Kerja dan Lingkungan Kerja Terhadap Kesejahteraan Subjektif Karyawan - Falti Manullang; Dian Surya Sampurna (Jurnal Riset Multidisiplin Edukasi, 2025)
Employee well-being has become an important indicator in measuring a company's success in managing human resources. This study aims to analyze the role of coping strategies in mediating the effect of work stress and work environment on employees' subjective well-being. This study uses a quantitative approach. The population in this study consists of all employees of XYZ Company, totaling 50 employees. This study uses data analysis methods using SmartPLS software version 3.2.7. PLS or Partial Least Square test is a structural equation modeling (SEM) approach based on variance. The results of this study found that work stress does not affect employees' subjective well-being. Work stress does not affect coping strategies. Work environment affects employees' subjective well-being. Work environment affects coping strategies. Coping strategies have a significant effect on employees' subjective well-being. Coping strategies mediate the effect of work stress on employees' subjective well-being insignificantly. Coping strategies mediate the effect of work environment on employees' subjective well-being insignificantly. Therefore, a supportive work environment, including positive relationships with colleagues and management, has been shown to increase employees' subjective well-being. Social support and resources provided by the work environment help employees choose more adaptive coping strategies. In addition, the use of adaptive coping strategies, both problem-focused and emotion-focused, contributes positively to employees' happiness and life satisfaction.